Orchid diversity of the cape of Kamenjak (Istria, Croatia) - Vukovic, Nina; Brana, Slavko; Mitic, Bozena (Acta Botanica Croatica, 2011)
Twenty two taxa have been recorded in the south of Istrian peninsula (north Adriatic coast, Croatia). The research was performed in the period 2003–2004. A great majority of taxa belong to Euri- Mediterranean (seven taxa, 41.18%) and Steno-Mediterranean (six taxa, 35.29%) floral elements. Eurasiatic (two taxa, 11.76%), Atlantic (one taxa, 5.88%) and endemic (one taxon, 5.88%) plants were also present. Almost a half of recorded orchids are abundant or frequent. The most of taxa are endangered s.l.; nine vulnerable (VU) plants (52.94%), and one species endangered s.s. (EN) (5.88%). There are also near threatened (NT) (two taxa, 11.76%), and data deficient (DD) (one taxon, 5.88%) plants, while others have no category assigned (four taxa, 23.53%).